PERAN KOMUNIKASI ORANG TUA DENGAN PIHAK SEKOLAH DALAM LAYANAN ANAK AUTISME DI LEMBAGA PENDIDIKAN ANAK USIA DINI INKLUSI - , Hermanto (Pendidikan Luar Biasa, 2012)
Abstract; One of the individuals with special needs are children with autism. Autism with various types and levels of both heavy and light, both are disorders of child development are very influential on subsequent developments. The effect of these developments, such as the ability of communication with others. They have difficulty interacting and expressing what they want. Children with autism early age with such a condition, are in need of intensive treatment in the form of therapy and teaching in an integrated way. Children with autism early age not only directly following their education in special schools, but many of them follow the process of play and interact in early childhood education institutions in general. It is very likely to occur because of several factors, for the communication between parents and teachers in this school is needed. The existence of effective communication between both parties, it would be very positive impact on growth and development of children with autism itself, and the groups of children or to the existence of these institutions.